Pengembangan Komik Keteladanan KH. A. Wahab Hasbullah Untuk Meningkatkan Keterampilan Berbicara Bahasa Arab - Yazmir Ganistan; Rina Dian Rahmawati (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2023)
Comics are one of the media that make a positive contribution to learning. The language used in conveying the message is direct, not convoluted so that it is easy for readers to remember and understand. This is very effective in overcoming various student problems in learning Arabic. The research objectives to be achieved in this study are to improve students' understanding of Arabic language learning with comic media. The research method used in this research is R&D (Research and Development), which aims to develop research. The steps taken are Planning, Production, and Evaluation. The results obtained in this study are an increase in student understanding of reading skills, increased student understanding in conversation, increased student ability in writing, and an increased ability to memorize vocabulary in Arabic.